Sugarcane leaf-derived organosolv lignin as antibacterial and antioxidant agents of natural rubber composites - Kamonwat Nakason; Parinvadee Chukaew; Yuwanda Thongpanich; Fuangfa Utrarachkij; Sanchai Kuboon; Wasawat Kraithong; Skulrat Pichaiyut; Wanwitoo Wanmolee; Bunyarit Panyapinyopol (Cleaner Materials)
To enhance the sustainability and carbon neutrality of natural rubber (NR) derived product, lignin extracted from sugarcane leaf (SCL) was incorporated into NR to prepare environmentally friendly antibacterial (AB) and antioxidant (AO) lignin/NR composites. In this study, SCL lignin was isolated via an organosolv process at different temperatures (140 – 180 °C) and using various organic solvents (ethanol, acetone, and isopropyl alcohol (IPA)). Disk diffusion susceptibility tests, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) demonstrated the AB efficacy of SCL organosolv lignin against Gram-positive bacteria (S. aureus) compared to Gram-negative bacteria (E. coli and S. Typhimurium). The choice of solvent gradually influenced the AB and AO performances of the lignin. Py-GC/MS analysis revealed that SCL organosolv lignin predominantly comprised p-hydroxyphenyl (H’) and guaiacyl (G’) with a minor presence of syringyl (S’) lignin. The incorporation of SCL organosolv lignin into NR showed that NR vulcanizates exhibited enhanced mechanical, AO, and AB properties, depending on the solvent type used in the organosolv process. The NR vulcanizates incorporated with L-Acetone showed dominant aging properties and AB efficacy. On the other hand, the tensile strength and elongation at break of the NR composites were significantly improved by L-IPA and L-Ethanol. These results suggest that SCL organosolv lignin, particularly L-IPA, could be an excellent alternative bio-filler for enhancing the mechanical, AO, and AB properties of NR composites.